Exploring policy options in regulating rural-urban migration with a Bayesian Network: A case study in Kazakhstan - Thomas Dufhues; Gertrud Buchenrieder; Zhanli Sun (The European Journal of Development Research, 2021)
Despite the benefits associated with the free movement of people, governments often try to regulate urban immigration by constraining the agency of potential rural out-migrants in moving to cities and/or in expanding their agency to enable them to stay put. We apply an institutional framework centring on push–pull and retain–repel factors to migration intentions of potential migrants in northern Kazakhstan. We model the effects of these factors on migration intentions with Bayesian Networks and expand the baseline model with three policy scenarios. The results suggest that the effects of policies constraining urban in-migration, e.g. limiting access to affordable housing, are attenuated by social networks and reverse remittances. The supply of accessible and appropriate information on possible income and true housing costs in urban areas presents a promising road to reduce intentions of rural out-migration. Better schools and decentralised tertiary education can also reduce the migration intentions of rural residents. – – En dépit des avantages associés à la libre circulation des personnes, les gouvernements tentent souvent de réguler l'immigration urbaine en limitant la capacité de potentiels émigrants ruraux à se déplacer vers les villes et / ou en élargissant leur capacité à rester sur place. Nous appliquons un cadre institutionnel centré sur les facteurs push-pull et les facteurs de rétention-répulsion liés aux intentions de migration de potentiels migrants dans le nord du Kazakhstan. Nous modélisons grâce aux réseaux bayésiens les effets de ces facteurs sur les intentions de migration et élargissons le modèle de référence avec trois scénarios de politiques publiques. Les résultats suggèrent que l'effet des politiques publiques limitant l'immigration urbaine, comme par exemple limiter l'accès à des logements à loyer abordable, est atténué par les réseaux sociaux et par les transferts de fonds inversés. Le fait de fournir des informations accessibles et pertinentes sur ce que l'on peut gagner, en termes de revenus, et sur ce que l'on doit dépenser pour se loger dans les zones urbaines représente une voie prometteuse pour réduire les intentions d'exode rural. De meilleures écoles et un enseignement supérieur décentralisé peuvent également réduire les intentions de migration des résidents ruraux.
Keywords: 300; Kazakhstan; migration policies; push-pull/retain-repel factors; migration intentions; policy scenarios; Bayesian Networks